2016
DOI: 10.3389/fphar.2016.00133
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Soluble Epoxide Hydrolase Limits Mitochondrial Damage and Preserves Function Following Ischemic Injury

Abstract: Aims: Myocardial ischemia can result in marked mitochondrial damage leading to cardiac dysfunction, as such identifying novel mechanisms to limit mitochondrial injury is important. This study investigated the hypothesis that inhibiting soluble epoxide hydrolase (sEH), responsible for converting epoxyeicosatrienoic acids to dihydroxyeicosatrienoic acids protects mitochondrial from injury caused by myocardial infarction.Methods: sEH null and WT littermate mice were subjected to surgical occlusion of the left ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 51 publications
3
32
0
Order By: Relevance
“…This EET-B treatment prior to ischemia in SHR could have additional effects on acute cardiac ischemic tolerance as suggested by the reduction of life-threating arrhythmias [ 19 ]. In addition, the improved post-MI LV function is more likely attributable to EET-B beneficial actions during CHF progression as it was previously demonstrated for other EET-based pharmacological interventions [ 8 , 10 , 11 , 18 , 37 , 48 ]. Finally, in a recent work we demonstrated that sEH inhibitor c-AUCB and EET analog EET-A, given alone or in combination at reperfusion attenuated the progression of post-MI LV systolic dysfunction only in Sprague-Dawley but not in hypertensive Ren-2 transgenic rats in spite of blood pressure reduction [ 19 , 49 ].…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…This EET-B treatment prior to ischemia in SHR could have additional effects on acute cardiac ischemic tolerance as suggested by the reduction of life-threating arrhythmias [ 19 ]. In addition, the improved post-MI LV function is more likely attributable to EET-B beneficial actions during CHF progression as it was previously demonstrated for other EET-based pharmacological interventions [ 8 , 10 , 11 , 18 , 37 , 48 ]. Finally, in a recent work we demonstrated that sEH inhibitor c-AUCB and EET analog EET-A, given alone or in combination at reperfusion attenuated the progression of post-MI LV systolic dysfunction only in Sprague-Dawley but not in hypertensive Ren-2 transgenic rats in spite of blood pressure reduction [ 19 , 49 ].…”
Section: Discussionmentioning
confidence: 66%
“…It has been shown that NUDSA, an earlier generation EET analog, improved cardiac function in mice after MI [ 18 ]. Moreover, an attenuation of post-MI LV dysfunction progression has been reported in rats and mice treated with various sEH inhibitors [ 8 , 10 , 11 , 37 , 48 ]. In line with these earlier findings, we demonstrated that EET-B treatment (started two weeks before MI and continued till seven weeks after MI) attenuated post-MI LV systolic dysfunction and adverse changes of ventricular geometry in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Ischemia-reperfusion injury can lead to accumulation of protective EETs after the release of fatty acids by membrane-bound phospholipases (Seubert et al, 2004). Increasing EETs in an sEH null mouse model showed limited mitochondrial damage after ischemia compared with wild-type (Akhnokh et al, 2016). EETs can enforce their cardioprotective effects through the activation of mitoK (ATP) and opening of the mitochondrial membrane permeability pore (Barau et al, 2015).…”
Section: Cyp2j2/eets In the Maintenance Of Cardiovascular Health: Amentioning
confidence: 99%
“…Furthermore, the treatment period used by Alsaad and colleagues may not be sufficient to induce many of the characteristic features of chronic DOX cardiotoxicity. A detailed assessment by Cove-Smith et al (2014) of both cardiac Cyclosporine A (Tang et al, 2011) Hypertension, tachycardia, myocardial infarction Oxidative stress and/or mitochondrial dysfunction In a CYP2J2 transgenic mouse, heart failure-induced oxidative stress was mitigated by EETs; EETs increased expression of antioxidant enzymes and reduced ROS levels (Wang et al, 2014;Akhnokh et al, 2016).…”
Section: Role Of Cyp2j2 In Dox-induced Cardiotoxicitymentioning
confidence: 99%
See 1 more Smart Citation